Formulation Development and Evaluation of Gum Damar Based Sustained Release Matrix Tablet of Metoprolol Succinate - Thombre, Nilima; Aher, Archana; Shimpi, Pranali (Asian Journal of Pharmaceutical Research and Development, 2020)
Background: An oral dosage form containing sustained released matrix tablet used the natural polymer in the replacement of synthetic polymer. Objective: To prepare sustained release matrix tablet using natural polymer damar & drug Metoprolol Succinate. Material and method: Metoprolol Succinate using Gum Damar as release retardant were prepared by wet granulation technique using 23 factorial design with the quantity of gum damar, concentration of the microcrystalline cellulose& dicalcium phosphate (DCP) as variables. Matrix tablets were prepared using different strengths of GD (10% to 30% w/w) with respect to total tablet weight and two different excipients DCP & microcrystalline cellulose as a diluents. The physicochemical properties such as hardness, thickness, friability, uniformity of weight and the drug content of the formulated tablets were estimated. The physico-chemical properties gum Damar was evaluated for its oral toxicity. Acute oral toxicity study was carried out according to OECD guideline 425 in the albino mice and study revealed that gum was nontoxic. Result & discussion: Developed sustained released matrix tablet posses hardness of 4.93 ± 0.25, Thickness of 4.74 ± 0.15, Content Uniformity (%) of 98.78 ± 0.52, Weight variation of 248.51 ± 2.12,Friability (%w/w) of 0.41 ± 0.024, In vitro drug release was found to be 95 ± 0.84 % in 12 hrs time, DSC thermogram study sharp endothermic peak was observed.The kinetics of release of Metoprolol Succinate was found diffusion. In vivo oral toxicity study showed no animal was died during study and it was observed that gum is nontoxic. Conclusion: A systematic study revealed that by selecting a suitable composition of Damar gum & dicalcium phosphate as a diluent, the desired dissolution profile could be achieved. The mechanism of drug released was found to be diffusion. Keywords:-